Patient safety in plastic surgery: a systematic review - Otto Huasckar Muchinski Saucedo; Elaine Rossi Ribeiro; Juliane Centeno Muller; Izabel Cristina Meister Martins Coelho (Revista Brasileira de Cirurgia Plástica)
Introduction: patient safety has become an increasingly present topic in health research. Plastic surgery is a specialty in evidence, and it is necessary to adapt patient safety to its particularities. Methods: Systematic review to investigate actions related to patient safety in plastic surgery. MEDLINE and SCIELO were chosen to locate the studies. The descriptors: "patient safety" and "plastic surgery" were used in the MEDLINE database. In SCIELO, the descriptors: "segurança do paciente" e "cirurgia plástica" were used. In both cases, the publication period was between 2012-2018, totaling 15 articles. Results: The countries that published the most on the subject were the United States and Brazil. The most frequent concern was safety related to the training of plastic surgery residents. Tools like the checklist have also been used to improve security. Another concern that requires more study will be if the weekends have higher complications with surgeries performed during the week. However, well-formulated medical records, as well as the Informed Consent Form (ICT), appear to have a more solid basis in patient safety. Pre-anesthetic consultation also seems to favor patient safety. Furthermore, finally, the use of WhatsApp seems to be a safe tool, and that improves the care provided by the medical team. Conclusion: The need for more in-depth studies on this topic is emphasized, considering that a systematized protocol was not found.